2000
DOI: 10.1074/jbc.m001116200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Functional Expression of cDNAs Encoding Methionine-sensitive and -insensitive Homocysteine S-Methyltransferases from Arabidopsis

Abstract: Plants synthesize S-methylmethionine (SMM) from Sadenosylmethionine (AdoMet), and methionine (Met) by a unique reaction and, like other organisms, use SMM as a methyl donor for Met synthesis from homocysteine (Hcy). These reactions comprise the SMM cycle. Two Arabidopsis cDNAs specifying enzymes that mediate the SMM 3 Met reaction (SMM:Hcy S-methyltransferase, HMT) were identified by homology and authenticated by complementing an Escherichia coli yagD mutant and by detecting HMT activity in complemented cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 40 publications
4
74
3
Order By: Relevance
“…Two methionine molecules are then regenerated from SMM by transfer of a methyl group from SMM to homocysteine. This second reaction is catalysed by homocysteine S-methytransferase (EC 2.1.1.10) (Giovanelli et al 1980;Ranocha et al 2000). SMM was identified as a major component in the phloem of several higher plant species (Bourgis et al 1999), suggesting that it has a role in the transport of methionine in plant tissues.…”
Section: Recycling Of Methioninementioning
confidence: 99%
“…Two methionine molecules are then regenerated from SMM by transfer of a methyl group from SMM to homocysteine. This second reaction is catalysed by homocysteine S-methytransferase (EC 2.1.1.10) (Giovanelli et al 1980;Ranocha et al 2000). SMM was identified as a major component in the phloem of several higher plant species (Bourgis et al 1999), suggesting that it has a role in the transport of methionine in plant tissues.…”
Section: Recycling Of Methioninementioning
confidence: 99%
“…At5g49810, a non-essential gene encodes methionine methyltransferase (EC 2.1.1.12) in A. thaliana (Tagmount et al, 2002;Kocsis et al, 2003). Extensive biochemical characterization, including in vitro enzyme assays and complementation of S. cerevisiae and E. coli mutations (Ranocha et al, 2000;Ranocha et al, 2001), demonstrated that homocysteine methyltransferase (EC 2.1.1.10) is encoded by three A. thaliana genes, At3g25900 (HMT1), At3g63250 (HMT2), and At3g22740 (HMT3). Whereas HMT1 is feedback-inhibited by methionine, HMT2 and HMT3 are not.…”
Section: The S-methylmethionine Cyclementioning
confidence: 99%
“…Whereas homocysteine methyltransferase forms two molecules of methionine from S-methylmethionine and homocysteine, methionine methyltransferase uses S-adenosylmethionine as a methyl group donor to form S-methylmethionine from methionine. Although homocysteine methyltransferase is also present in bacteria, fungi, and animals, methionine methyltransferase has been found only in plants (Ranocha et al, 2000). At5g49810, a non-essential gene encodes methionine methyltransferase (EC 2.1.1.12) in A. thaliana (Tagmount et al, 2002;Kocsis et al, 2003).…”
Section: The S-methylmethionine Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…It shares significant sequence homology with homocysteine Smethyltransferases (HMT). Despite the fact that both SMT and HMT enzymes catalyze methyl transfer using S-methylmethionine as the methyl donor, they exhibit significant Secontaining (for SMT) and S-containing (for HMT) substrate choice as a methyl acceptor in vitro (Neuhierl and Bock, 1996;Ranocha et al, 2000). SMT was found to be constitutively expressed in roots and leaves of A. bisulcatus, and appear to be not affected by Se induction (Pickering et al, 2003).…”
Section: Phytoremediation and Biofortificationmentioning
confidence: 99%